1993
DOI: 10.1093/nar/21.23.5323
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic removal of 5-methylcytosine from DNA by a human DNA-glycosylase

Abstract: DNA 5-methylcytosine is a major factor in the silencing of mammalian genes; it is involved in gene expression, differentiation, embryogenesis and neoplastic transformation. A decrease in DNA 5-methylcytosine content is associated with activation of specific genes. There is much evidence indicating this to be an enzymic process, with replacement of 5-methylcytosine by cytosine. We demonstrate here enzymic release of 5-methylcytosines from DNA by a human 5-methylcytosine-DNA glycosylase activity, which affords a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 41 publications
3
46
1
Order By: Relevance
“…5-MeC is apparently removed and replaced by cytosine by an enzymic mechanism resembling the BER process [171]. While one report suggested that 5-meC is removed by an endonucleolytic process [172], others have demonstrated release of the free base (5-meC, which is subsequently deaminated to thymine) by HeLa nuclear extracts [173]. Recently, release of 5-meC by a partially purified enzyme from HeLa cells [174] and by a highly purified enzyme from chick embryos [175] was reported, indicating that a DNA glycosylase activity is responsible for 5-meC removal.…”
Section: -Mec-dna Glycosylasementioning
confidence: 99%
“…5-MeC is apparently removed and replaced by cytosine by an enzymic mechanism resembling the BER process [171]. While one report suggested that 5-meC is removed by an endonucleolytic process [172], others have demonstrated release of the free base (5-meC, which is subsequently deaminated to thymine) by HeLa nuclear extracts [173]. Recently, release of 5-meC by a partially purified enzyme from HeLa cells [174] and by a highly purified enzyme from chick embryos [175] was reported, indicating that a DNA glycosylase activity is responsible for 5-meC removal.…”
Section: -Mec-dna Glycosylasementioning
confidence: 99%
“…Recently, Vairapandi and Duker proposed an alternative pathway for removal of5-MeC involving a 5-MeC-specific DNA glycosylase (6). They found that incubation of a [methyl-3H]poly(dG-5-methyl-dC) polymer with a HeLa cell nuclear extract caused the release of radioactivity in an ethanolsoluble form.…”
Section: Introductionmentioning
confidence: 99%
“…One potential mechanism to achieve this is through the action of 5-methylcytosine DNA glycosylase, which removes the methylcytosine from DNA leaving the deoxyribose intact (10). Local DNA repair then removes the abasic nucleotide and adds back an unmethylated cytosine nucleotide (11). Using chicken embryo nuclear extracts that can promote demethylation (12), a putative demethylase was purified; this was found to be a G͞T mismatch repair DNA glycosylase (13).…”
mentioning
confidence: 99%